Cross-Border Mergers and Acquisitions and Financial Development: Evidence from Emerging Asia - Douglas H. Brooks; Juthathip Jongwanich (Asian Development Bank (ADB), 2011)
The paper examines the relationship between cross-border mergers and acquisitions (M&A) and financial development in emerging Asian economies. Bilateral data of cross-border M&A for nine emerging Asian economies during 2000–2009 are analyzed with a sample selection model and panel data model. Estimation results show that the banking sector plays a crucial role in facilitating cross-border M&A while the role of equity markets has increased in importance since, in addition to cash, the issuance of common stock and the exchange of stocks have become a popular form for payment for a deal. Because of the relatively thin market, the corporate bond market plays a limited role in supporting cross-border M&A, which is in contrast to the public bond market. The results also show that financial development in terms of stock and bond markets in the home countries tends to be more important when the target firms reside in more developed countries. In addition to financial development, the paper shows that most of the cross-border M&As are invested in the technology-related and resource-based industries while cheap labor industries are relatively less attractive.
hdl:11540/2053
Keywords: F21; F24; G10; O53; 330; Foreign direct investment; mergers and acquisitions; financial development; Übernahme; International; Unternehmensfinanzierung; Kreditgeschäft; Asien